KONTRIBUSI USAHATANI KENTANG TERHADAP PENDAPATAN KELUARGA DI DESA MANEMBO KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - Rendi Joyke Maramis; Noortje M. Benu; Martha M. Sendow (Sam Ratulangi University, 2021)
This study aims to analyze the contribution of potato farming to family income in Manembo Village, Passi Timur District, Bolaang Mongondow Regency. This research was conducted from January to March 2020. The main data used were primary data obtained through interviews with 30 (thirty) respondents of selected potato farmers using a simple random sampling method. The analytical method used in this research uses quantitative descriptive analysis and is presented in tabular form. The data analyzed included: income analysis and contribution analysis. The results showed that the amount of income received by potato farmers in Manembo Village, East Passi District was IDR 5,105,256.48, with a contribution of 84.70% to family income. This shows that potato farming on the total income of farmer families is in the high category, which indicates that potato farming is the main source of income for most of the farmer families in Manembo Village, or in other words farmers are very dependent on potato farming as the main livelihood for meet all the necessities of family life.